Robust maximum power point tracking control for photovoltaic system based on second order sliding-mode - A. Fezzani; N. Bouarroudj; S. Drid; L. Zaghba (Institute of Advanced Engineering and Science, 2020)
This paper proposes a control approach of a maximum power point of a photovoltaic (PV) system using the second order sliding mode approach. The main objective of the proposed paper is to track the maximum power point (MPP) using super twisting algorithm (STA) with a one-loop control method and augment efficiency of the output power system. The structure of a proposed approach is simple and robust aging the atmospheric changes. Such control approach solution has several advantages such as simple implementation, robustness; reduce the chattering phenomenon and good dynamic response compared to traditional first-order sliding mode control algorithm. The controller circuit adapts the duty cycle of the switch electronic device of the DC/DC converter to search maximum power point tracking as a function of evolution of the power input. The effectiveness and feasibility of the proposed control are verified by simulation in MATLAB/Simulink environment and dSPACE-based hardware in loop platform.